2012
DOI: 10.5435/jaaos-20-05-310
|View full text |Cite
|
Sign up to set email alerts
|

Safe Tourniquet Use: A Review of the Evidence

Abstract: Due in part to an emphasis on quality and cost control within healthcare institutions, protocols for healthcare practice are increasingly being developed in an effort to maintain normative guidelines and set acceptable standards. For example, the Association of periOperative Registered Nurses, the National Quality Forum, and the Association of Surgical Technologists have made recommendations regarding tourniquet use. In the institution of the senior authors (C.D. and E.A.), an effort to establish a protocol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 58 publications
2
85
0
6
Order By: Relevance
“…Assuming that tourniquet and transport times are nearly equivalent, our recorded transport times took 31 (23, 39) minutes, which is considerably shorter than the 2 hours used for tourniquets in the operating room. 45, 46 However, it is difficult to conclude that the limited observation of complications would be observed regardless of tourniquet time or in a setting with an immature trauma system with prolonged transport times. The retrospective nature of this study additionally limited the abstraction of specific information regarding location of the five nerve palsies in relation to the level of the tourniquet.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that tourniquet and transport times are nearly equivalent, our recorded transport times took 31 (23, 39) minutes, which is considerably shorter than the 2 hours used for tourniquets in the operating room. 45, 46 However, it is difficult to conclude that the limited observation of complications would be observed regardless of tourniquet time or in a setting with an immature trauma system with prolonged transport times. The retrospective nature of this study additionally limited the abstraction of specific information regarding location of the five nerve palsies in relation to the level of the tourniquet.…”
Section: Discussionmentioning
confidence: 99%
“…This “2-hour window” was derived from a considerable body of evidence from animals and clinical studies, which clearly show that tourniquet use produces morphological, electrophysiological, and functional impairments that are significant and increase in severity as tourniquet duration increases, but appear, in general, to be reversible with time (12). A review from 2012 entitled “Safe Tourniquet Use: A Review of the Evidence” included eight “high-quality clinical studies” to support the recommendation that, “while early electrophysiological changes and muscle atrophy are detectable, long-term functional differences are rare, and outcomes between standard tourniquet and no-tourniquet groups are equivocal’ (see Fitzgibbons et al , 2012 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Included are brief reviews of the mechanisms governing muscle protein synthesis and degradation as well as cell and endoplasmic reticulum (ER) stress responses. To supplement this brief review, readers are encouraged to take advantage of the many excellent published reviews which cover relevant areas: immune and complement activation of IR injury (3), signaling pathways controlling translation (36), mitochondrial reactive oxygen species generation (31), ER stress and mitochondrial involvement in cell survival (26), ER stress in skeletal muscle (7), clinical perspective on safe tourniquet use (12), and cell biology of IR injury (18). …”
Section: Introductionmentioning
confidence: 99%
“…It has been recommended that TT be limited to 2 h in human studies due to the increase in postoperative complications caused by an extended TT [10]. Investigating the relationship between TT and postoperative complications in arthroplastic knee surgery, Olivecrona et al [17] found an increase in postoperative complications including wound leakage, local injury due to TP, nerve damage, compartment syndrome, deep venous thrombosis, and pulmonary embolism with every 10-min increment in TT.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on healthy volunteers have suggested that the TT should be limited to 2 h [1, 4, 10]. The risk of systemic complications increases with time, especially in patients with morbid obesity, a history of peripheral vascular surgery, and severe left-ventricular dysfunction, as well as in elderly and trauma patients [1].…”
Section: Introductionmentioning
confidence: 99%